Reductive acetogenesis is a dominant process in the ruminant hindgut - Qiushuang Li; Jiabin Huo; Gaofeng Ni; Fan Zhang; Shizhe Zhang; Xiumin Zhang; Rong Wang; Jinzhen Jiao; Zhongtang Yu; Xuanxuan Pu; Yipeng Yue; Emilio M. Ungerfeld; et al. (Microbiome)
Abstract Background The microbes residing in ruminant gastrointestinal tracts play a crucial role in converting plant biomass to volatile fatty acids, which serve as the primary energy source for ruminants. This gastrointestinal tract comprises a foregut (rumen) and hindgut (cecum and colon), which differ in structures and functions, particularly with respect to feed digestion and fermentation. While the rumen microbiome has been extensively studied, the cecal microbiome remains much less investigated and understood, especially concerning the assembling microbial communities and overriding pathways of hydrogen metabolism. Results To address this gap, we comparatively investigated the composition, capabilities, and activities of the rumen and the cecum microbiome using goats as an experimental ruminant model. In situ measurements showed significantly higher levels of dissolved hydrogen and acetate in the cecum than in the rumen. Increased dissolved hydrogen indicated distinct processes and reduced coupling between fermentative H2 production and utilization, whereas higher levels of acetate could be caused by slower VFA absorption through cecal papillae than through the rumen papillae. Microbial profiling indicated that the cecum harbors a greater abundance of mucin-degrading microbes and fermentative hydrogen producers, whereas the rumen contains a higher abundance of fibrolytic fermentative bacteria, hydrogenotrophic respiratory bacteria, and methanogenic archaea. Most strikingly, reductive acetogenic bacteria were 12-fold more abundant in the cecum. Genome-resolved metagenomic analysis unveiled that the cecum acetogens are both phylogenetically and functionally distinct from those found in the rumen. Further supporting these findings, two in vitro experiments demonstrated a marked difference in hydrogen metabolism pathways between the cecum and the rumen, with increased acetate production and reduced methanogenesis in the cecum. Moreover, comparative analysis across multiple ruminant species confirmed a strong enrichment of reductive acetogens in the hindguts, suggesting a conserved functional role. Conclusions These findings highlight an enrichment of acetogenesis in a key region of the gastrointestinal tract and reshape our understanding of ruminant hydrogen metabolism and how the H2 can be managed in accord to livestock methane mitigation efforts. Video Abstract